Analysis of Ornamental Plant Farming Income in Bangun Sari Baru Village, Tanjung Morawa District - Wahyu Isnanda Nasution; Sarah Dian Anjani; Adhiana Adhiana; Cut Rozana Sari; Sakral Hasby Puarada (Jurnal Mahasiswa Agribisnis, 2025)
This research was carried out in Bangun Sari Baru Village, Tanjung Morawa District. This study aims to analyze the income of ornamental plant farming, analyze whether or not ornamental plant farming is feasible in Bangun Sari Baru Village. The background of this research is that from the beginning of 2000 to 2020, ornamental plant farming activities were in great demand by the people of Bangun Sari Baru Village because they were considered to have good business prospects to be developed. However, in the midst of this potential, ornamental plant farmers in Bangun Sari Baru Village began to face challenges in the form of selling price instability, rising production costs, and dependence on seasonal demand patterns. This condition causes fluctuations in income felt by farmers. This study was conducted on 34 ornamental plant farmers in Bangun Sari Baru Village, Tanjung Morawa District. The research methods carried out are quantitative methods with income analysis, feasibility analysis with R/C ratio approach and B/C ratio. The results of the study show that the average net income received by ornamental plant farmers is IDR 2,708,015.51 per month. The results of the feasibility analysis obtained an R/C Ratio value of 2.36 and a B/C Ratio of 1.36, which means that ornamental plant farming activities are classified as feasible and economically profitable.